Determınatıon And Comparısıon Of Anxıety Of Patıents And Parents Before Orthodontıc Treatment - Ali İhya Karaman; Zafer Sarı; Tancan Uysal; Nurten Sargın; Ömer Üre (Galenos Yayinevi, 2001)
Anxiety is one of the usual daily psychologic reaction which contribute positive to human's behaviour. It sends people learn and investigate. But when the degrees of anxiety increase, people's behaviours change too much. Over anxious people resist taking what they are given and percieve small problems as a matter of life or death. They are too much excited during medical examination, continuously tense and their emotional reactions are exaggarated. They are always afraid and reluctant in cooperation and they never take responsibility. On the other hand patient cooperation is a must in orthodontic treatment achieving succesful results with a noncomplient patient is not likely. The aim of this study was the determination and comparision of anxiety levels of patients and parents before orthodontic treatment; evaluation of the factors which increase the anxiety level and for succesful treatment take the necessary measures to decrease this. A personal knowledge form and STAI TX-1 and STAI TX-I1 anxiety inventories were apllied to randomly selected seventy patients and their parents in the Orthodontic Department of Selçuk University, Faculty of Dentistry. Results were subjected to statistical evaluation using one way ANOVA and student's t-tests in the computer with SPSS for Window's release. Results of this study indicate that STAI TX-1 anxiety level of the patients and STAI TX-II anxiety level of the parents who were abaut to start an orthodontic treatment was high and we saw that communication problems were affect this levels. As a conclusion we suggest determining the anxiety levels of patients and parents, eliminate the potential factors which affect tis levels and have a good communication between patients and parents; before orthodontic treatment.